A Functional Indel Polymorphism Within MIR155HG Is Associated With Sudden Cardiac Death Risk in a Chinese Population - Zhang, Qing; Yu, Huan; Yang, Zhenzhen; Li, Lijuan; He, Yan; Zhu, Shaohua; Li, Chengtao; Zhang, Suhua; Luo, Bin; Gao, Yuzhen (Frontiers in Cardiovascular Medicine, 2021)
Sudden cardiac death (SCD) is a devastating complication of multiple disease processes and has gradually became a major public health issue. miR-155 is one of the best characterized miRNAs and plays a critical role in several physiological and pathological process, including cardiovascular diseases. In this study, we systematically screened the whole region of miR-155 host gene (MIR155HG) and identified a 4-bp insertion/deletion variant (rs72014506) resided in intron region of MIR155HG as the candidate polymorphism. The association of rs72014506 with SCD susceptibility was evaluated using 166 SCD cases and 830 healthy controls in Chinese populations. Logistic regression analysis suggested that homozygote del/del genotype significantly decreased the risk of SCD [odds ratio (OR) = 0.29; 95% confidence interval (CI) = 0.12-0.74; Ptrend = 0.0004]. Further genotype-expression association study using human myocardium tissue samples suggested that the deletion allele was intimately linked to lower expression of both MIR155HG and mature miR155. Luciferase activity assay also revealed that the deletion allele of rs72014506 inhibited gene transcriptional activity. Finally, we performed electrophoretic mobility shift assay and verified the preferential binding affinity of the deletion allele with POU2F1 (POU domain class 2 transcription factor 1). Collectively, we have successfully identified a SCD risk conferring polymorphism in the MIR155HG gene and a likely biological mechanism for the decreased risk of SCD associated with the deletion allele. This novel variant may thus serve as a potential genetic marker for SCD diagnosis and prevention in natural populations, if validated by further studies with larger sample size.